Habitat and ecological diversity influences the species-area relationship and the biogeography of the Sicilian archipelago's isopods. Issue 1 (1st January 2018) - Cazzolla Gatti, R.; Messina, G.; Ruggieri, M.; Dalla Nora, V.; Lombardo, B. M.
Abstract: Terrestrial isopods are a well-studied invertebrate taxon in Sicily and in the surrounding islands (Maltese archipelago included). During the last 30 years their systematics, ecology and biogeography have been analysed by many authors. The size and the diverse geological origin of the Sicilian archipelago represents an ideal open laboratory in which to study some biogeographical patterns, such as the species-area relationship (SAR). Since many species show limited adaptation to broad physiological conditions and low mobility, and, therefore, their active dispersion is very slow, SAR can be a useful means to examine biogeographical patterns of isopods. Here we analyse their biogeography and whether there is a relationship between the area and the habitat variability of the island surveyed, and whether these factors have an either direct or coupled influence on species richness and ecology. Moreover, we evaluate a potential relationship between Isopoda species richness and the distance from the centre of dispersion (Sicily). Finally, we test for a difference in species and habitat richness between volcanic and non-volcanic islands. Our results show a positive correlation between the area and the habitat, more significant than that between the area and the species, leading us to speculate that habitat diversity has an influence on the SAR of isopods. We find a significantly higher richness of both species and habitats on non-volcanic islands. Finally, our analysis confutes the hypothesis that the number of isopod species on the archipelago's islets declines with the distance from Sicily. We suggest some potential explanations.